Psychometric evaluation of the Indonesian Nomophobia Questionnaire among college students: Measurement invariance across gender and levels of problematic smartphone use - Muthmainnah Muthmainnah; Kamolthip Ruckwongpatr; Ira Nurmala; Lutfi Agus Salim; Asma Nadia; Yuli Puspita Devi; Annisa Clara Salsabila; Musheer A. Aljaberi; Mark D. Griffiths; Chung-Ying Lin (Acta Psychologica, 2025)
With increasing technology advancement, including the rising use of smartphones, some individuals rely heavily on smartphones in their daily lives and become increasingly anxious if they do not have access to their smartphones (i.e., nomophobia [no mobile phobia]). The present study evaluated the psychometric properties of the Indonesian version of the Nomophobia Questionnaire (NMP-Q) to evaluate its validity and reliability among Indonesian university students aged 18 to 24 years. Each item and the structure of the Indonesian NMP-Q were tested using confirmatory factor analysis (CFA). Multi-group CFA (MGCFA) was employed to examine whether different genders, individuals with different levels of problematic smartphone use, and those with different time spent on social media use (more or less than five hours daily) interpreted the NMP-Q similarly. Moreover, Pearson correlations were used to examine how the NMP-Q was associated with other measures. After removing Item 1 of Factor III, the total and individual factor scores of the NMP-Q exhibited very good internal consistency (α = 0.76–0.93; ω = 0.76–0.92), The total and individual factor scores of the NMP-Q exhibited very good internal consistency (α = 0.76–0.93; ω = 0.76–0.92). The four-factor structure of the NMP-Q was supported and was invariant across different genders, different levels of smartphone use, and different daily time spent on social media. The NMP-Q was associated more strongly with problematic smartphone use (r = 0.17–0.41; p < .001) than with measures of weight-related self-stigma and psychological distress (r = 0.13–0.23; p < .001). The Indonesian NMP-Q is a reliable and valid instrument for assessing nomophobia among Indonesian university students, which researchers and healthcare providers can use in their research and/or clinical practice.